Kentucky Bluegrass: Perennial Ryegrass Seeding Ratios and Post‐Seeding Herbicides Affect Species Composition of Fairways. Issue 1 (1st July 2019) - Sousek, Matthew D.; Reicher, Zachary J.
Abstract : Core Ideas: On new fairways with limited annual bluegrass pressure, seeding ratios of 50–80% Kentucky bluegrass and 50–20% perennial ryegrass (by weight) should provide quick cover and result in primarily Kentucky bluegrass stands three years after seeding. In areas with substantial annual bluegrass pressure, seed ratios of 80% or more Kentucky bluegrass can compete with annual bluegrass and resulted in coverage of 80% or more Kentucky bluegrass three years after seeding when treated with annual bluegrass herbicides shortly after seeding and annually thereafter. Initiating an annual bluegrass control program shortly after seeding and maintaining this program thereafter is important to maximize Kentucky bluegrass coverage and minimize annual bluegrass coverage. In the Great Plains of the United States, mixtures of Kentucky bluegrass (KBG) and perennial ryegrass (PRG) are used to establish or renovate golf course fairways or interseed existing fairways after summer damage. Kentucky bluegrass is the preferable permanent species in the Great Plains, whereas PRG is used primarily for quick germination and establishment. Stand composition is affected by weather, management factors, and weed competition such as from annual bluegrass (ABG) and thus is difficult to predict from any given seed mixture of KBG and PRG. Our objective was to follow species composition for 3 years in fairway‐height stands seeded in mid‐August with different ratios of KBG and PRG and treated immediately after seeding and yearly thereafter with annual bluegrass herbicides. On the research site with almost no ABG competition, all seeding mixtures (50–100% KBG: 50–0% PRG wt:wt) except 100% PRG produced turf stands with > 94% KBG cover 3 years after seeding. There were no adverse effects of multiple applications of ethofumesate or mesotrione starting 4 weeks after seeding (WAS) in spite of these applications being earlier than label recommendations. On the site with substantial ABG pressure, increasing PRG in the seed mixture hastened turf coverage, and seed ratios of 80% or more KBG resulted in ≥ 80% KBG coverage after 3 years. Moreover, initiating ABG herbicides applications shortly after emergence and again each fall maximized short‐term turf establishment and KBG coverage after 3 years, as well as minimized ABG coverage after 3 year.